The Degree of Applying Active Learning Strategies – Field Study on English Language Teachers in Deir Alla Educational Directorate - Jordan– - Alghragheer, Bayan Ayed; Alghragheer, Ola Ayed (Journal of Educational and Psychological Sciences, 2021)
This study aimed to reveal the degree of applying active learning strategies among English language teachers from the points of view of basic stage students in Deir Alla educational directorate. To collect the data, Active Learning Strategy scale was applied among English language teachers consisting of (41) items. The study sample consisted of (244) basic stage students in (7th, 8th, 9th) grade. The results of the study showed that the degree of applying active learning strategies among English language teachers from the points of view of basic stage students was (3.72) with relative importance of (74.4%). The results showed significant statistical differences were found in degree of applying active learning strategies due to the effect of gender variable in favor of females, but there was no statistically significant difference attributable to the effect of the grade level, Finally, the results of the study showed that there were statistically significant differences attributed to the effect of the interaction between gender and grade level was found.